2018
DOI: 10.1371/journal.pone.0195263
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the olfactory system in the induction of anti-fatigue effects by odorants

Abstract: Some components of the neural circuits underlying innate odor-evoked responses have recently been elucidated. Odor information detected by the olfactory receptors is transmitted from the olfactory bulb to the cortical amygdala, where physiological and emotional states such as attraction or avoidance are controlled. Thus, activation of specific olfactory receptors can elicit changes in physiological and/or psychological state. Here, we examined on the odorant Hex-Hex Mix, which has been reported to induce anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
1
14
0
3
Order By: Relevance
“…In addition, agitation and cognitive impairment (language deficit or attention deficit) showed an interactive effect on OI in NPSs, consistent with previous research that olfactory dysfunction, cognitive impairment and agitation are strongly associated with each other. Regarding to the relationships between agitation and OI, previous studies have indicated that numerous brain regions related to agitation also participate in the olfactory circuit, such as the hippocampus, amygdala, insula, orbitofrontal cortex and habenula nucleus ( 30 , 31 ). Most studies found that the application of olfactory stimulation using essential oils, such as lavender or lemon, could improve the symptoms of agitation ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, agitation and cognitive impairment (language deficit or attention deficit) showed an interactive effect on OI in NPSs, consistent with previous research that olfactory dysfunction, cognitive impairment and agitation are strongly associated with each other. Regarding to the relationships between agitation and OI, previous studies have indicated that numerous brain regions related to agitation also participate in the olfactory circuit, such as the hippocampus, amygdala, insula, orbitofrontal cortex and habenula nucleus ( 30 , 31 ). Most studies found that the application of olfactory stimulation using essential oils, such as lavender or lemon, could improve the symptoms of agitation ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have linked OR stimulation with the anti-stress benefits of essential oil inhalation. However, findings by Saito et al [ 41 ] support that the known anti-fatigue effects of a certain mix of odorants involves activation of six olfactory receptors (OR1A1, OR2J3, OR2W1, OR5K1, OR5P3, and OR10A6). Fatigue is a prevalent condition often related to excessive workload and psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Human ORs and other genes were cloned as described earlier [ 38 , 39 ]. Briefly, all human OR genes and trace amine-associated receptor (TAAR) genes were amplified from human genomic DNA (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%